2021
DOI: 10.1007/s10531-021-02185-9
|View full text |Cite
|
Sign up to set email alerts
|

Vanishing permanent glaciers: climate change is threatening a European Union habitat (Code 8340) and its poorly known biodiversity

Abstract: The cryosphere (i.e. glaciers and permafrost) and its related landforms offer a wide range of ecosystem services, thus they have strong relationships with human population. Even if these harsh environments have often been regarded as inhospitable, there is a growing amount of literature on glacial biodiversity, specifically concerning European mountains. Glaciers and permafrost-related landforms (e.g. rock glaciers) host a variety of cold-adapted taxa, from bacteria to vertebrates. They have been included in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…These organisms appear to be differentiated among isolated glacial areas (Deharveng 1975;Lauga-Reyrel & Lauga 1995). By comparing different European glacier forelands, Hågvar et al (2020) observed how the species belonging to this group, and to a few other pioneer genera, are important not only as components of supraglacial communities (see also Gobbi et al 2021), but also as early colonisers of recently-deglaciated terrains. High diversity of cryophilic Isotomidae was observed in southern Alaska and in the Canadian Rocky Mountains in North America (Fjellberg 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These organisms appear to be differentiated among isolated glacial areas (Deharveng 1975;Lauga-Reyrel & Lauga 1995). By comparing different European glacier forelands, Hågvar et al (2020) observed how the species belonging to this group, and to a few other pioneer genera, are important not only as components of supraglacial communities (see also Gobbi et al 2021), but also as early colonisers of recently-deglaciated terrains. High diversity of cryophilic Isotomidae was observed in southern Alaska and in the Canadian Rocky Mountains in North America (Fjellberg 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Among these cold-adapted species, Desoria and taxonomically related genera like Agrenia Börner, 1906, Gnathisotoma, Myopia andKaylathalia Stevens &D'Haese, 2016 (Najt 1981;Fjellberg 2010;Stevens & D'Haese 2017) include cryophilic species (Potapov 2001;Fjellberg 2007Fjellberg , 2010. Cryophilic species, in particular, are of great interest because they are particularly threatened by the current global warming and are good candidates as indicators for conservation projects aimed at investigating refugial glaciated areas (Gobbi et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Glaciers, permafrost, and recently deglaciated areas are ecosystems in their own right and provide permanent or temporary habitat for a variety of specialized taxa from bacteria to vertebrates (Ficetola, 2021;Gobbi et al, 2021). The loss of mountain cryosphere-glacier and permafrost-and changes of the physiognomy of the emerging proglacial landscape threaten local high alpine biodiversity and ecosystems, such as altered hydrological, thermal and bio-geochemical cycles, glacier-fed streams, and glacier forelands (Brighenti et al, 2019).…”
Section: High Elevation (Alpine) Ecosystems and Biodiversitymentioning
confidence: 99%
“…The "winners" are more generalist and competitive species that benefit from the higher temperatures and colonize from lower elevations. Expected long-term effects include the loss of high alpine biodiversity, especially for the cold adapted taxa and high elevation endemic floras (Cuesta et al, 2020;Gobbi et al, 2021). These expected biological extinctions within proglacial systems will lead to ecological cascading effects on aquatic and terrestrial systems (Cauvy-Fraunié et al, 2016).…”
Section: High Elevation (Alpine) Ecosystems and Biodiversitymentioning
confidence: 99%
See 1 more Smart Citation